2021
DOI: 10.1016/j.heliyon.2021.e07334
|View full text |Cite
|
Sign up to set email alerts
|

The effects of knowledge sharing and person–organization fit on the relationship between transformational leadership on innovative work behavior

Abstract: Previous studies reveal a gap in the literature regarding the role of knowledge-sharing behavior and person--organization fit as mediating variables in assessing the impact of transformational leadership on innovative work behavior. Additionally, some studies show that transformational leadership and person-organization fit influence innovative work behavior, while other studies have found that they do not. This study investigates the effects of transformational leadership, person-organization fit, and knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
2
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 44 publications
5
30
2
4
Order By: Relevance
“… 5 , 6 Innovative behavior is defined as the process of asking questions and conceiving solutions, seeking support for one’s ideas, and realizing one’s innovative ideas. 14 In view of the above, students’ innovative behavior is defined as a series of changes in which they generate innovative ideas and try to put them into practice in the process of learning and participating in scientific and technological activities.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“… 5 , 6 Innovative behavior is defined as the process of asking questions and conceiving solutions, seeking support for one’s ideas, and realizing one’s innovative ideas. 14 In view of the above, students’ innovative behavior is defined as a series of changes in which they generate innovative ideas and try to put them into practice in the process of learning and participating in scientific and technological activities.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Likewise, by proposing a new model of leadership that promotes innovative behaviors, and due to the inclusion of different styles of leadership, this research contributes to reduce the knowledge gap observed in the literature. Up to date, the results of thesis studies are not conclusive (Sudibjo & Prameswari, 2021).…”
Section: Discussionmentioning
confidence: 94%
“…Although it is well known that leadership is an important driver of employees' IWB, results are not conclusive and there is an important gap in this regard that should be addressed by studying the type of leadership that encourages it in the organizations (Sudibjo & Prameswari, 2021). This study presents a new construct named "Innovational Leadership", that contributes to fill this gap.…”
Section: Introductionmentioning
confidence: 92%
“…They can stimulate teachers to achieve goals beyond expectations and peruse them to pass self-interest for the school's common values (Zeinabadi, 2013). To foster knowledge-sharing, transformational leaders create a positive culture at school by setting values associated with teaching-related knowledge and providing sufficient resources that facilitate knowledge-sharing activities among teachers (Sudibjo and Prameswari, 2021).…”
Section: Theoretical Perspectivementioning
confidence: 99%